Pengaruh Metode Pembelajaran Role Playing terhadap Hasil Belajar Siswa Kelas III UPTD SDN Kamal 2 pada Mata Pelajaran Pendidikan Pancasila - Bayu Sabilha Naufal; Nilamsari Damayanti Fajrin (Mataram University, 2026)
This study aimed to determine whether the use of the Role Playing learning method has a significant effect on the learning outcomes of third-grade students at UPTD SDN Kamal 2 in the Pancasila Education subject. The novelty of this study lies in the implementation of the Role Playing learning method on the topic of rights and responsibilities in Pancasila Education based on the Merdeka Curriculum for third-grade elementary school students. This research employed a quantitative approach using an experimental research design. The study adopted a quasi-experimental design with a nonequivalent control group design. The research sample consisted of all 40 third-grade students at UPTD SDN Kamal 2, who were divided into an experimental class and a control class. Data were collected through classroom observations and achievement tests. The test instrument was examined for validity, reliability, and item difficulty. The prerequisite analyses included normality and homogeneity tests, while the research hypothesis was tested using an independent samples t-test. The findings revealed that the calculated t-value (t = 2.490) was greater than the critical t-value (t = 2.024), with a significance value of 0.017 (< 0.05). Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. These results indicate that the implementation of the Role Playing learning method has a significant positive effect on the learning outcomes of third-grade students in the Pancasila Education subject at UPTD SDN Kamal 2. The findings also suggest practical implications for teachers, indicating that the Role Playing learning method can serve as an innovative instructional strategy to enhance students' participation, engagement, and academic achievement, particularly in learning about rights and responsibilities within Pancasila Education.